Complications of Bezoar in Children: What Is New? - Kam Lun Ellis Hon; Jean Cheng; Chung Mo Chow; Hon Ming Cheung; Kam Lau Cheung; Yuk Him Tam; Alexander K. C. Leung (Case Reports in Pediatrics)
A bezoar is a mass found trapped in the gastrointestinal system. The condition may be associated with pica, especially in developmentally retarded children. Clinical manifestations are usually nonspecific. Endoscopic diagnosis and removal of the foreign materials is often indicated. Occasionally, severe complications may occur. We report two cases to illustrate the clinical features and complications in these children. In the first case, a reliable history was not obtained in the developmentally delayed girl which precluded prompt diagnosis, but the grossly dilated stomach on plain abdominal radiograph gave clues to an underlying insidious mechanical obstruction of upper gastrointestinal tract. In the second case of a normal child, the unrelenting symptoms and weight loss prompt further investigations which revealed the diagnosis. Literature on pediatric bezoar is reviewed. Oesophagoduodenoscopy is the investigation of choice for diagnostic confirmation, but surgical facilities must be available to deal with acute complications.